Aplicación de las normas de cuidados obstétricos y neonatales esenciales (CONE) de primer nivel en el Subcentro de Salud de Yangana del Distrito 11D01 Loja Salud. - Castro Mendoza, Sandy Gabriela (2016)
The objectives in this study were to evaluate the application of the rules of essential obstetric and neonatal care through the guidance of the Ministry of Public Health in the health sub center of Yangana the 11D01 district in the period February to October 2015, determine compliance with the standard of essential obstetric and neonatal care, assess the knowledge that the operational staff, make proposals from results. The study was quantitative, descriptive and prospective survey to all pregnant women was conducted, postpartum women and health team knowledge CONE also review the registration matrix CONE was done. With a sample of 39, which corresponds to the universe and shows including 29 pregnant women, 3 and 7 postpartum health staff members who met the inclusion criteria, with the following results: In applying CONE found that 75% does not apply and the remaining 25% yes; CONE compliance in 75% not given proper complimiento and 25% is followed correctly; CONE knowledge through the operational staff found that 57.14% averagely know one if they know 28.57% and 14.28% do not know one. It being evident that is not performing the application of CONE and in contrast to this the lack of knowledge by health personnel, pregnant and postpartum women Keywords: maternal mortality, care, pregnancy, newborn, childbirth, postpartum health team